Gut microbes and muscle function: can probiotics make our muscles stronger?. Issue 3 (12th March 2022) - Giron, Muriel; Thomas, Muriel; Dardevet, Dominique; Chassard, Christophe; Savary‐Auzeloux, Isabelle
Abstract: Evidence suggests that gut microbiota composition and diversity can be a determinant of skeletal muscle metabolism and functionality. This is true in catabolic (sarcopenia and cachexia) or anabolic (exercise or in athletes) situations. As gut microbiota is known to be causal in the development and worsening of metabolic dysregulation phenotypes such as obesity or insulin resistance, it can regulate, at least partially, skeletal muscle mass and function. Skeletal muscles are physiologically far from the gut. Signals generated by the gut due to its interaction with the gut microbiome (microbial metabolites, gut peptides, lipopolysaccharides, and interleukins) constitute links between gut microbiota activity and skeletal muscle and regulate muscle functionality via modulation of systemic/tissue inflammation as well as insulin sensitivity. The probiotics able to limit sarcopenia and cachexia or promote health performances in rodents are mainly lactic acid bacteria and bifidobacteria. In humans, the same bacteria have been tested, but the scarcity of the studies, the variability of the populations, and the difficulty to measure accurately and with high reproducibility muscle mass and function have not allowed to highlight specific strains able to optimize muscle mass and function. Further studies are required on more defined population, in order to design personalized nutrition. For elderly, testing the efficiency of probiotics according to the degree of frailty, nutritional state, or degree of sarcopenia before supplementation is essential. For exercise, selection of probiotics capable to be efficient in recreational and/or elite athletes, resistance, and/or endurance exercise would also require further attention. Ultimately, a combination of strategies capable to optimize muscle functionality, including bacteria (new microbes, bacterial ecosystems, or mix, more prone to colonize a specific gut ecosystem) associated with prebiotics and other 'traditional' supplements known to stimulate muscle anabolism (e.g. proteins), could be the best way to preserve muscle functionality in healthy individuals at all ages or patients.